Feasibility and Safety of Food Containing Acanthopanax senticosus for Treating Patients with Cancer-Related Fatigue - Yutaka Kawano; Nanae Watanabe; Masahiko Nishiyama; Tousei Ohmura; Hiroyoshi Mihara; Kaoru Ono; Maki Tanaka; Yasushi Sato; Tetsu Tomonari; Hidekatsu Takeda; Tetsuji Takayama (Palliative Medicine Reports)
Background: Cancer-related fatigue (CRF) is a major obstacle to quality of life. Acanthopanax senticosus Harms (ASH) is available as a botanical adaptogen food worldwide. Objective: This study aimed to assess the feasibility and safety of ASH in patients with CRF. Methods: Fifteen patients with CRF consumed ASH drink for 28 days. The primary endpoint was the completion rate of the study, and the secondary endpoints were changes in brief fatigue inventory (BFI), oxidative stress markers, and adverse events. Results: Seven patients successfully completed the study. Four patients who had BFI <5.5 at enrollment revealed a decrease in BFI. The biological antioxidant potential/diacron-reactive oxygen metabolites ratio, potential antioxidant capacity, was increased but not significant (p = 0.063). No adverse events attributable to ASH were observed. Conclusions: Approximately 50% patients were successful in consuming ASH for 28 days. Patients with mild CRF showed improvement by using ASH. However, further investigations are needed to validate these findings.